A survey of morphological, molecular, and histopathological characteristics of Taenia pisiformis metacestode in Egyptian rabbits (Oryctolagus cuniculus) - Ras, Refaat; El-Bahrawy, Amanallah; Abdelkhalek, Adel; Morariu, Florica; Elsayed, Ayman N.; Nouh, Doaa S.; Plesko, Anamaria; Ilie, Marius Stelian; AbdelMageed, Manar (Frontiers in Veterinary Science, 2025)
IntroductionTaenia pisiformis (T. pisiformis), the etiological agent of cysticercosis in rabbits, poses a considerable health risk to domestic lagomorphs and contributes to economic losses in rabbit farming. This study aimed to ascertain the prevalence, risk factors, and molecular characteristics of T. pisiformis in rabbits from three Egyptian regions: Badr City (Cairo Province), Sadat City (Monufia Province), and Assiut City (Assiut Province).MethodsA total of 150 samples were collected from both home-raised (n = 77) and farm-raised (n = 73) rabbits from January 2024 to December 2024. T. pisiformis cysts were identified morphologically and histologically, with tissue samples processed using hematoxylin and eosin (H&E) staining. Molecular confirmation was performed using polymerase chain reaction (PCR) targeting the cytochrome oxidase subunit 1 (cox1) and NADH dehydrogenase subunit 1 (nad1) mitochondrial genes, followed by sequencing and phylogenetic analysis. Statistical associations between infection and risk factors (age, location, season, and management system) were evaluated using the chi-square test and Fisher’s exact test.ResultsThe overall infection prevalence rate was 21.3% (32/150), which was significantly higher in home-raised rabbits (31/77, 40.2%) than in farm-raised rabbits (1/73, 1.3%; χ2 = 31.5, p < 0.001). Infection rates were also strongly linked to season, with fall and winter showing higher prevalence. Cysts were mostly found in the mesentery and varied in number (1–5 per rabbit). Morphologically, the cysts contained a scolex with distinctive features, including suckers and rostellar hooks. Histology showed a thick cyst wall and characteristic tissue structures. Molecular analysis confirmed the parasite as T. pisiformis, with sequence similarities ranging from 97.64 to 100%, indicating a close relationship to global sequences.DiscussionThese findings underscore the influence of management practices and seasonal factors on infection dynamics and highlight the importance of molecular tools in parasite surveillance.